Application of Segmentation, Targeting, Positioning, and Differentiation in CV Slimeday Indonesia’s Slime Advertisements as a Sensory Play Medium for Children Aged 5-6 Years - Devina Putri Sholikhah; Bayu Setiawan; Aryo Bayu Wibisono (Golden Ratio of Data in Summary, 2026)
This paper aims to examine the stages involved in developing an advertising strategy for sensory play-based children's toys produced by CV Slimeday Indonesia. Slime, as the company's flagship product, is considered an effective medium for supporting children's motor development, particularly during the golden age of early childhood. The advertisement is designed to communicate the educational benefits of sensory play in a manner that is clear, engaging, and easily understood by consumers. The development process employs the STPD (Segmentation, Targeting, Positioning, and Differentiation) framework to create a targeted and effective promotional strategy. This approach facilitates the analysis of digital marketing strategies by considering demographic, psychographic, geographic, and behavioral consumer characteristics, enabling the identification of appropriate target markets and the articulation of the product's unique selling proposition (USP). As a result, the strategy produces well-directed and effective short-form video advertisements for digital platforms, including TikTok, Instagram, and e-commerce video channels.